2020
DOI: 10.1016/j.foodres.2020.109518
|View full text |Cite
|
Sign up to set email alerts
|

How consumers’ perception and information processing affect their acceptance of genetically modified foods in China: A risk communication perspective

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 53 publications
6
47
0
Order By: Relevance
“…Likewise, the result of MG-CFA verified the substantial variance in the influence of the attitude on acceptance of GMF across the four groups. This is also consistent with past studies that affirmed that the public, in case of community or market acceptance, remain more mindful to choice regarding sensitive things, such as food [ 19 , 20 ]. However, interestingly, it was validated that the valence or frame of issues (health), which is considered more personal and can be more concerning to them, remained more effective (β = 0.52).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Likewise, the result of MG-CFA verified the substantial variance in the influence of the attitude on acceptance of GMF across the four groups. This is also consistent with past studies that affirmed that the public, in case of community or market acceptance, remain more mindful to choice regarding sensitive things, such as food [ 19 , 20 ]. However, interestingly, it was validated that the valence or frame of issues (health), which is considered more personal and can be more concerning to them, remained more effective (β = 0.52).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, messages from well-respected sources can be an effective way to develop acceptance. The results of H1 about the direct influence of knowledge on perceived risk reduction (group 1 β = 0.22, group 2 β = 0.27, group 3 β = 0.09, and group 4 β = 0.07) are consistent with several psychological theoretical paradigms that describe how individuals observe threats and how they process risk information to act [ 20 , 39 ]. For instance, our results showed that participants that were exposed to the ad messages containing expert opinions experienced a greater reduction in perceived risks about GMF (see Figure 4 ).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Most people do not possess elaborated knowledge about GMF [ 20 , 80 , 81 ]. One way to cope with this lack of knowledge and capacities is to rely on others to evaluate and manage an associated hazard.…”
Section: Research Hypotheses and Frameworkmentioning
confidence: 99%